Creditor protection and government procurement contracting - Liu, Xiao; Ma, Zhiming; Ruan, Lufei (Journal of Accounting and Economics, 2025)
This paper examines the effect of creditor protection on the choice of government procurement contract types. We use the staggered adoption of anti-recharacterization laws (ARLs) as a quasi-natural experiment to investigate the research question. ARLs strengthen creditors’ rights to repossess collateral in bankruptcy and thus enhance creditor protection. Using a dataset of U.S. government contracts, we find a significant shift from the use of fixed-price contracts to cost-plus contracts after the adoption of ARLs. The effect is more pronounced for firms with higher default risk and stronger firm-government ties. We also find that the government is more likely to switch away or reduce the contract value for contractors affected by ARLs. Overall, our findings point to an important relation between debt contracts and government contracts.